Comparison of Uplift Capacity and Nonlinear Failure Surfaces of Single-Belled Anchor in Homogeneous and Layered Sand Deposits - Tanaya Deb; Sujit Kumar Pal (Advances in Civil Engineering)
This experimental study explains the contribution of embedment ratios, diameter ratios, and bell angles to uplift capacities of single-belled anchors and formation of nonlinear failure surfaces in homogeneous and layered sand deposits. Uplift capacities in both types of sand deposits are increased with higher embedment ratios, lesser diameter ratios, and bell angles. Uplift capacities are higher in layered sand deposit in comparison with homogeneous sand deposit for the same model. Analytical uplift capacities are predicted by the horizontal slice method based on observed failure surfaces. A comparative discussion is made on nonlinear failure surfaces as well as analytical uplift capacities in reference to aforementioned parameters for the variation in sand deposits. The 45° and 63° belled anchors are more effective as uplift-resistant structures than 72° anchors in both types of sand deposits. Out of 36 analytical data on homogeneous sand and 33 analytical data on layered sand, 94.45% data are within the range of +08.51 to −10.70% and 100% data are within the range of +10.47 to −10.72%, respectively, with respect to the experimental uplift capacities. Four numbers of multiple linear regression models have been developed by observed breakout factors to eliminate the size effect, so the newly developed models are suitable for actual engineering to compare with prototype tests within the suggested imitation of values of variable parameters.